An Analytical Model to Identify Brake System Vibration within the Low Frequency Domain - Magaswaran, K.; Phuman Singh, A.S.; Hassan, Muhammad Zahir (SAE International, 2013)
This paper presents the analytical model of a brake system to investigate the low frequency vibration. The purpose of this study is to model and validate brake system vibration. The brake model was developed by applying the theory of sinusoidal traveling waves and wave super positioning. An experimental modal analysis (EMA) of the brake disc has been carried out to obtain the natural frequencies. Wave equations were then formulated based on the experimental data. These waves are super positioned to be shown as a single spatial and temporal function that will provide periodic excitation to the brake pad. The brake pad was modeled as a beam element with distributed friction force. The differential equations were solved using Green's dynamic formulation. The model is capable of predicting vibration behavior of the brake pad for whole range below 1 kHz which has shown strong agreement with the experimental results validated through in-house brake dynamometer. This brake model can serve as a tool to investigate the relationship between braking parameters and other variables within the brake system.